Tunable polarization-induced Fano resonances in stacked wire-grid metasurfaces - Xavier Romain (Nature Portfolio, 2021)
Fano resonance is an important phenomenon for optical devices particularly for application in switching and sensing. Here, the authors demonstrate theoretically and experimentally that Fano resonances can be induced using the polarization dependent properties of stacked wire-grid metallic metasurfaces.